Father's responsibility and child support : a review of evidences from Shariah Courts in Malaysia - Kahar, Rojanah; Hasbullah @ Abdullah, Muslihah (2012)
Islamic law emphasizes that fathers should play their duties and obligations toward their children within the family system regardless during marriage or after divorce. The ideal fathers in Islam should value the needs of children as well as adults, give children a balance of boundaries and love and are involved in calculating character of reverence to Allah. As the child grows, the physical needs such as shelter, food, drink and extendable to medication and education for upbringing of the child. By using the theory of maqasid al shariah, this paper attempts to examine the relationship between father’s responsibility and payment of child support in Malaysia. Content analysis from the Shariah Courts cases, are given emphasis in analyzing the implementation of Islamic Family Law relating to child support and its consequences on children’s wellbeing. It is anticipated that failure of receiving good treatment and financial support from father in the event of divorce affects the national agenda of sustaining future generations. The current trends also posit some challenges in ensuring the smooth implementation of social policy and law in Malaysia.